Strategy for Creating New Entrepreneurs: Training on Making Purple Sweet Potato Sticks as a Solution for Improving Community Economy - Teguh Setiawan Wibowo; Nurul Hidayati (North Press, 2026)
This community service activity aims to improve the knowledge and skills of mothers in the Keputih area, Surabaya, in processing purple sweet potatoes into economically valuable stick products, as well as fostering entrepreneurial motivation as an effort to increase family income. The activity was held on June 12, 2026, at Pos PAUD Terpadu Tunas Mulia, Keputih, Surabaya, involving 15 mothers as participants. The implementation method used a participatory and educational approach through three main sessions, namely the presentation of material on the economic potential and nutritional content of purple sweet potatoes, hands-on practice of making purple sweet potato sticks covering all production stages from material preparation to packaging, as well as discussion and evaluation sessions. This activity involved IKBIS undergraduate nutrition students as assistant facilitators and presented Dr. apt. Teguh Setiawan Wibowo, MM., MBA., M.Si., M.Farm., AIFO and Ir. Rr. Nurul Hidayati, M.Si., A.Md.Akup as resource persons. The results showed that there was an increase in participants' understanding of the economic potential of purple sweet potatoes, hygienic processing techniques, calculation of capital and business profits, and product marketing strategies, as evidenced by the results of the pre-test and post-test evaluations. All participants expressed enthusiasm and interest in starting an independent business based on processing purple sweet potato sticks at home. This activity makes a real contribution to improving the family economy amid the burden of economic pressure, while building community economic independence and resilience through optimal utilization of local potential. Sustainable mentoring programs are recommended to ensure the sustainability of participants' businesses.